Relations that Show the Network Potential for Spatial Data Sharing - Fatih Taktak; Hulya Demir (Tehnički Vjesnik, 2019)
Physical and functional cooperation based on a certain hierarchy among public institutions, local governments, private sectors and all other industries that work with spatial data is a very important dynamic. This cooperation between organizations or individuals is actually built with unofficial networks that are not bound by predefined rules. By utilizing network analysis, a formal presentation of the existing collaborations and communication networks can be made.The questions that were asked to organizations during the research were selected to determine various issues such as their collaborations within the network, data exchange potential and awareness to understand the direction of the flow. This study provided an insight into the organizations that should be prioritized in any regulation and initiative on the spatial data infrastructure (SDI). Furthermore, it is proposed that organizations that are currently less active with spatial data can play a more active role with the quantitative and qualitative increase in e-applications.